COST-BENEFIT ANALYSIS OF HUMAN RESOURCES - Świątek, Władysław (Scientific Journal of Bielsko-Biala School of Finance and Law, 2015)
Entering the new millennium and knowledge-based economy, it became undeniable that people, not money, buildings and equipment are the primary and most important determinant of the quality of companies and their future. This means that one of the most important elements of modern enterprise management is the management of human resources. This paper describes the elements of the Balanced Scorecard adapted to human resources, and methods of calculation and estimation of costs and benefits of these resources.